Sound of One Hand Clapping: Information Disclosure for Social and Political Action for Accountability in Extractive Governance in Mozambique - Awortwi, Nicholas; Nuvunga, Adriano (IDS, 2019)
Corruption through opaque public contracts costs Africa billions of dollars in revenue loss annually. Globally, initiatives to address this have centred on information disclosure (ID) but under what conditions does it work to promote accountability in the extractive sector that for a long time has seen its revenue management as being a major cause of conflict in Africa? Our study on this issue in Mozambique reveals intriguing findings, which suggest that protagonists of ID would need to recalibrate their strategies for promoting accountability. The study on ID in extractive governance in Mozambique has found 17 factors that connect to result in citizen and institutional inaction in demanding government accountability. The lessons from the study for policy and practice are that unless there is a link between ID and a government’s reputation, which scales up to the risk of a ruling government losing power, accountability is unlikely to occur when new information is disclosed.
Accepted: 2019-01-28T16:38:12Z ISSN: 2040-0209
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; corruption / corrupção; decentralization / descentralização; extractive industries / indústrias extractivas; natural resources / recursos naturais

Relatório De Diagnóstico Sobre Transparência, Governação E Corrupção - República de Moçambique (International Monetary Fund (IMF), 2019)
A economia de Moçambique encontra-se num ponto de viragem, e os esforços para abordar as vulnerabilidades em matéria de governação e corrupção podem ter um impacto positivo duradouro. Já tomámos medidas para abordar as vulnerabilidades em matéria de governação e corrupção. Contudo, reconhecemos que subsistem falhas em diversas áreas relevantes da economia. A fim de abordar algumas das debilidades restantes, temos reformas de governação em curso e em perspectiva em várias áreas, muitas delas apoiadas por diversos doadores. Reconhecemos que a implementação eficaz continua a suscitar preocupações. Reconhecemos que a falta de transparência pode igualmente exacerbar as preocupações com a governação e agravar o risco de conflitos de interesse. Embora reconheçamos que temos um papel essencial a cumprir na melhoria da governação e no combate à corrupção, não podemos fazê-lo sozinhos. Estamos preparados e dispostos a tomar medidas concretas.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; accountability / responsabilização; corruption / corrupção; transparency / transparência